2014
DOI: 10.3109/00207454.2014.957760
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic brain injury (TBI) presenting with Guillain-Barre syndrome and elevated anti-ganglioside antibodies: a case report and review of the literature

Abstract: Guillain-Barré Syndrome (GBS) is a demyelinating polyneuropathy resulting in sensory, motor and autonomic symptoms. The severity of the disease can range from mild to severe but it is classically described as an ascending demyelinating process. Initially thought to be the sequelae of a bacterial or viral infection, the clinical symptoms of post-infective GBS can present up to 4 weeks after sentinel injury. A rarely defined post-surgical GBS has been since described after major cranial, cardiothoracic and gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“… Staff et al (2010) [ 2 ] 21 F/11 65 (24–83) Surgery within 30 days Neuropathy with active denervation; Increased epineurial perivascular inflammation;17 patients had increased axonal degeneration. Huang et al (2015) [ 3 ] 4 M/4 57 (50–69) Spine Surgery: within 1 week Neuropathy and 2 cases with active denervation not done Scozzafava et al (2008) [ 4 ] 1 M/1 28 (28) Spinal cord injury within 1 day Severe axonal polyneuropathy not done Tan et al (2010) [ 5 ] 1 M/1 44 (44) Head injury 1 week Neuropathy with active denervation; Presence of lymphocytes and severe axonal degeneration. Al-Hashel et al (2013) [ 6 ] 2 F/1 39 (31–47) Traumatic bone injury within 1 week 1 with features of mixed axonal and demyelinating neuropathy not done Rivas et al (2008) [ 7 ] 1 M/1 55 (55) Head injury 1 week An inexcitability of all nerves with active denervation; A severe loss of myelinated axons without significant demyelination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Staff et al (2010) [ 2 ] 21 F/11 65 (24–83) Surgery within 30 days Neuropathy with active denervation; Increased epineurial perivascular inflammation;17 patients had increased axonal degeneration. Huang et al (2015) [ 3 ] 4 M/4 57 (50–69) Spine Surgery: within 1 week Neuropathy and 2 cases with active denervation not done Scozzafava et al (2008) [ 4 ] 1 M/1 28 (28) Spinal cord injury within 1 day Severe axonal polyneuropathy not done Tan et al (2010) [ 5 ] 1 M/1 44 (44) Head injury 1 week Neuropathy with active denervation; Presence of lymphocytes and severe axonal degeneration. Al-Hashel et al (2013) [ 6 ] 2 F/1 39 (31–47) Traumatic bone injury within 1 week 1 with features of mixed axonal and demyelinating neuropathy not done Rivas et al (2008) [ 7 ] 1 M/1 55 (55) Head injury 1 week An inexcitability of all nerves with active denervation; A severe loss of myelinated axons without significant demyelination.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma is defined as any physical damage to the body caused by violence or accident. The concept of post-traumatic GBS was recently introduced and defined as GBS preceded by no risk factors other than trauma [ 4 ]. To date, there appears to have been no systematic analysis of the clinical and electrophysiological features of GBS following trauma.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Disintegration of the BBB during neurotrauma leads to the accumulation of localized T lymphocytes and macrophages, which may induce the transformation of microglial cells in the nervous system into antigen presenting cells. [3,11,12] Activated microglia can present post traumatic neuronal debris to the immune system and stimulate B cells to produce antibodies against the myelin sheath, causing demyelination, especially in the peripheral nervous system. [13] The explanation of GBS following head trauma or hemorrhage may be that some substances originating in the central nervous system, usually being weakly immunogenic, are transported through the disrupted BBB to the peripheral nervous system where they cause demyelination or axonal damage.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Some studies have shown that nearly 80% of AMAN patients are anti-ganglioside antibody positive, especially within the first week of onset. [4] The best treatment for GBS is IVIg or plasma exchange, both of which aim to remove antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation